Budaya Kerja dari Perspektif Kristen dan Implementasinya dalam Realisasi Dana Otonomi Khusus di Papua - Banga, Berthin Samuati; Roragabar, Yeni Irawati (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2022)
Papua is one of the provinces that has received special autonomy funds from the Government of the Republic of Indonesia. This policy's main objective is to increase Papua's human development index. The fact is that the human development index in Papua has not increased significantly. This is related to the work culture of implementing the policy, which is not yet optimal. Given that some policy implementers are Christians, it is very important to explore the concept of work culture according to Christian teachings so that it can guide them. This research aims to explore Christian teachings about work culture and their relevance in the management of the special autonomy policy in Papua. The method used is a literature study. The results of the study show that there are four aspects of work culture in Christian teaching that are relevant to optimally implemented in implementing the special autonomy policy in Papua. The four work cultures are work motivation, work goals, work functions, and forms of work that are pleasing in the eyes of God.